2018
DOI: 10.3892/mco.2018.1673
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large B‑cell lymphoma with pulmonary and cerebral involvement: A case report

Abstract: Primary diffuse large B-cell lymphoma (DLBCL) is the most common type of non-Hodgkin lymphoma; however, the involvement of the lung and central nervous system (CNS) in patients with DLBCL is rare. Furthermore, patients with DLBCL rarely exhibit specific clinical symptoms, which may delay definitive diagnosis. The present study reports the case of a 42-year-old man suffering from primary DLBCL with concurrent pulmonary and cerebral involvement. The patient suffered from human immunodeficiency virus infection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The cell-specific semantic network helps to reveal the pathways those are triggered by the potential markers and finally leads to metastasis. Furthermore, from literature it is observed that patients suffering from DLBCL are at high risk of brain diseases 13 . For brain diseases, the pathways need to cross the blood brain barrier.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell-specific semantic network helps to reveal the pathways those are triggered by the potential markers and finally leads to metastasis. Furthermore, from literature it is observed that patients suffering from DLBCL are at high risk of brain diseases 13 . For brain diseases, the pathways need to cross the blood brain barrier.…”
Section: Resultsmentioning
confidence: 99%
“…The first two aforementioned markers have worked as a downstream transcription factor for WNT signaling pathway 14 . This pathway plays a key role in the development and maintenance of embryo, metabolism and cellular growth 13 as well as involves in the progression of carcinoma 18 . During the development of T cells from T cells, the expressions of these two markers are decreased.…”
Section: Role Of Cell Type-specific Pathways In Dlbcl In Disruption O...mentioning
confidence: 99%